Analisis Putusan Hakim Dalam Tindak Pidana Lingkungan Hidup Oleh Korporasi (Jurnal Begawan Hukum (JBH), 2024)
This research aims to analyze the judge's decision regarding environmental crimes committed by corporations through Decision Number 190/Pid.B/LH/2020/PN Plw. This research uses a type of normative research with three approaches for the purposes of legal analysis and explanation, namely the case approach, statutory approach and conceptual approach. In contrast to previous research, this research specifically describes how judges interpret judges' interpretations in deciding cases of environmental crimes committed by corporations in more detail, not only from a criminal law perspective but also from the perspective of environmental law itself. The results of this research show that the Defendant in the "a quo" case is not a human being/person who can physically act and speak in front of the court, but rather a corporation with a legal entity, so in this case the Defendant PT. APAI must be represented by its administrator, namely Mr. GKE who is the Director of PT. WHAT. The defendant's actions were categorized as gross negligence because they reflected very serious negligence because they had a significant impact and were detrimental to the wider community. The defendant was not sentenced to prison but was only sentenced to a minimum fine in accordance with the provisions of Article 99 Paragraph (1). The defendant was also sentenced to additional punishment or disciplinary action in the form of reparation for the consequences of the criminal act even though this article was not included in the prosecutor's indictment. The additional punishment imposed is in the form of the amount of costs required to improve the environment in the amount of land that has been determined by taking into account the polluter pays principle and the precautionary principle. For this reason, the imposition of additional criminal sanctions should be decided by considering the concept of sustainable and environmentally sound development by taking into account various aspects including social, economic and environmental.